Membentengi Generasi Muda: Penanaman Nilai-Nilai Pancasila untuk Mencegah Korupsi - Syawang, Sirilus Daniel Agung; Muhammad Ilham Iskandar; Crist Evan Lamhot Turnip; Darrell Hammam Luthfiadi; Haikal Putra Gustiansyah; Mufti Malik Falhadi; Yayang Furi Furnamasari (Indo-MathEdu Intellectuals Journal, 2024)
Corruption has become a serious problem that undermines the foundations of morals and society. Corruption is not only economically damaging, but also threatens the integrity of the nation and state. Combating corruption is not only the task of the government, but also requires the active role of the community from all social layers, especially the younger generation who are the future successors of the nation. This study aims to determine the importance of instilling Pancasila values to fortify the younger generation from acts of corruption. The research was conducted using a qualitative case study method. Information was collected through observation of documents from scientific articles by entering keywords: Pancasila, corruption, young generation. The data analysis technique used is inferential, by generalizing the information obtained and processing the information to more specific information. The results of this study show the importance of instilling Pancasila values as the key to forming anti-corruption characters in the younger generation to achieve the ideals of the country